1995
DOI: 10.1016/0012-821x(95)00053-f
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetism and magnetic fabrics from the Springdale and Wigwam Redbeds of Newfoundland and their implications for the Silurian paleolatitude controversy

Abstract: In many mobile belts, paleomagnetic directions from elastic sedimentary rocks are typically shallower than directions from associated igneous rocks. This discordance raises questions about the reliability of sedimentary rocks and can lead to controversial paleogeographic reconstructions. In Newfoundland, the controversy over Silurian paleogeography arises from a difference between results from elastic redbeds (with anomalously shallow directions that place Newfoundland at the paleoequator in the Silurian) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Similar type of behaviour has been reported by Hodych & Hayatsu (1988) on the basis of their palaeomagnetic results from Jurassic red beds. Contrary to these views some of the researchers (Tucker 1979; Stamatakos et al . 1995; Tan et al .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Similar type of behaviour has been reported by Hodych & Hayatsu (1988) on the basis of their palaeomagnetic results from Jurassic red beds. Contrary to these views some of the researchers (Tucker 1979; Stamatakos et al . 1995; Tan et al .…”
Section: Discussionmentioning
confidence: 82%
“…Similar type of behaviour has been reported by Hodych & Hayatsu (1988) on the basis of their palaeomagnetic results from Jurassic red beds. Contrary to these views some of the researchers (Tucker 1979;Stamatakos et al 1995;Tan et al 2007) have observed that fine-grained magnetic minerals, which carry magnetically hard component and distributed spectra of unblocking temperatures, have accurately recorded magnetic field directions without any inclination error. However, higher degree of inclination shallowing have been observed by them in the coarse-grained sediments, which carry magnetically soft NRM component and discrete unblocking spectra.…”
Section: Inclination Shallowing In Sandstone and Mudstone Layersmentioning
confidence: 91%
“…Studies by Anson and Stamatakos et al [1994] have criticized Hodych and Buchan's approach, since they believe that AIR inadequately determines the magnetic fabric in all the remanence-carrying hematite grains. Stamatakos et al [1995] have subsequently provided detailed evidence that the anomalously shallow inclinations in the Silurian redbeds from Newfoundland are due to magnetic overprints dominating the remanence in coarse-grained sandstones.…”
Section: Introductionmentioning
confidence: 99%
“…u Smethurst and McEnroe (2003),. v Stamatakos et al (1995),. w. Johnson and Van der Voo (1985), x Thompson et al (2010),.…”
mentioning
confidence: 97%